Effect of flushing velocity and flushing duration on sediment transport in microirrigation driplines - Puig-Bargués, Jaume; Lamm, Freddie R. (My University, 2014)
Dripline flushing is a maintenance procedure that is recommended for all microirrigation systems. However, flushing velocity and flushing duration, which particularly affect the design and management of subsurface drip irrigation (SDI) systems, have not been studied extensively. For a better understanding of the flushing process in driplines and manifolds, a laboratory study was conducted at Kansas State University with a 10 m transparent pipe simulating an SDI dripline. Three different sediments with sizes up to 500 µm were introduced into the pipeline, and their distribution along the pipeline was analyzed under different flushing velocities over various times. Head loss under the conditions of this study increased exponentially with increased flushing velocity, suggesting that the flow regimes could be characterized between moving beds and heterogeneous flow. The percentage of pipeline blockage was logarithmically related to the flushing velocity, with greater than 30% of the pipeline occupied by larger sand sediments when the flushing velocity was less than 0.3 m sˉ¹. Although flushing velocities at or near the calculated deposition velocity could remove the majority of the sediments with a short duration of 15 min or less, flushing velocities that were approximately 45% to 65% of the deposition velocity could achieve similar sediment removal with longer flushing duration (up to 180 min). The ASAE EP-405 recommended minimum flushing velocity of 0.3 m sˉ¹ still appears adequate for most microirrigation systems operating under typical conditions. Designers are encouraged to calculate the deposition velocity for new microirrigation systems and to use it as a flexible guideline to assess the adequacy of flushing. End-users are encouraged to extend the duration of flushing for perhaps as long as 5 min after the initial concentration of sediments are removed to improve overall flushing. Further research is warranted to evaluate flushing velocity, but the results of this study should be representatively instructive of the phenomenon of sediment transport in microirrigation driplines during flushing.
Keywords: Drip irrigation; Dripline flushing; Emitter clogging; Microirrigation; Pipeline sedimentation